Analisis Efektivitas Video “Good Health And Well-Being-Nory” Berbasis Motion Graphic Menggunakan EPIC Model - Adhe Tertiasusman; Teddy Setyawan (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Many people think that people who are physically fitis a healthy person, whereas a healthy person is a person whophysically and mentally or physically healthy. When mental healthIf a person's spirituality is disturbed, he will experience health problemsMental health In Indonesia alone, there are around 14 million people over the age of 15years with mental health problems. One of the solutions thatoffered from the problem is through the "NORY" application, which is an application thatintended for teenagers who have problems with healthmentally packaged in the form of a motion graphics-based videoand then analyzed its effectiveness using the EPIC Modelwhich consists of several dimensions, namely Empathy, Persuasion, Impact andCommunications. Then it is calculated whether the video has been effectiveaccording to the EPIC Model or EPIC Rate scale range.